2009
DOI: 10.3354/dao02000
|View full text |Cite
|
Sign up to set email alerts
|

Protection of rainbow trout from infectious hematopoietic necrosis (IHN) by injection of infectious pancreatic necrosis virus (IPNV) or Poly(I:C)

Abstract: It was recently reported that prophylaxis against infectious hematopoietic necrosis virus (IHNV) in fish was induced by pre-exposure to the infectious pancreatic necrosis virus (IPNV). Here the establishment of IHNV immunity in rainbow trout Oncorhynchus mykiss was investigated by IHNV challenge following non-lethal pre-infection with IPNV. Also, synthetic double-stranded RNA polyinosinic polycytidylic acid, Poly(I:C), an inducer for interferon (IFN), was evaluated as a substitute for IPNV induction of the non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 33 publications
(49 reference statements)
0
33
0
Order By: Relevance
“…For IHNV infection in rainbow trout, it has been thoroughly documented that, within the first few days of infection, the host response is dominated by a strong induction of numerous interferon-stimulated genes, including Mx-1 [22]. In addition, pre-treatment of rainbow trout with injection of Poly(I:C), a TLR-3 agonist, offers significant protection from infection and mortality following challenge with IHNV [23]. For displacement pair 1, Mx-1 expression in fish exposed to genotype 007 was significantly higher than that in fish exposed to genotype 111 at day four post-infection, but not on any other day.…”
Section: Resultsmentioning
confidence: 99%
“…For IHNV infection in rainbow trout, it has been thoroughly documented that, within the first few days of infection, the host response is dominated by a strong induction of numerous interferon-stimulated genes, including Mx-1 [22]. In addition, pre-treatment of rainbow trout with injection of Poly(I:C), a TLR-3 agonist, offers significant protection from infection and mortality following challenge with IHNV [23]. For displacement pair 1, Mx-1 expression in fish exposed to genotype 007 was significantly higher than that in fish exposed to genotype 111 at day four post-infection, but not on any other day.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies using ELISA systems for the detection of specific fish antibodies have been reported for aquatic animals (Jorgensen et al 1991;Yoshimizu et al 1992;Dixon et al 1994;Pilström 1994, 1995;LaPatra 1996;Nishida et al 1998;Watanabe et al 1998;Swain and Nayak 2003;Okuda et al 2006;Kim et al 2007Kim et al , 2008Kim et al , 2009Takami et al 2010). However, use of an ELISA for fish antibody detection can be problematic because of difficulties such as low reproducibility, which is partly due to high background optical density (OD) caused by nonspecific reactions between fish antibodies and antigens Pilström 1994, 1995;Knopf et al 2000;Kibenge et al 2002;Guo and Woo 2004).…”
mentioning
confidence: 98%
“…The time between primary and secondary virus challenge was not a controlled factor in this study; therefore, conclusions could not be made about the importance of time between infections on viral replication in superinfection. In addition to these, many studies have investigated the effect of concurrent multiple infection with viruses of different species in natural and model hosts (4,29,31,(33)(34)(35). Thus, the dynamics of in vivo superinfection with variants of the same viral species have yet to be extensively defined for a vertebrate RNA virus and may provide insight into the mechanisms behind many of the field observations of superinfection for other important vertebrate viruses.…”
mentioning
confidence: 99%